Przygotowanie uczniów do międzynarodowych certyfikatów językowych Fit in Deutsch 1 i 2 jako sposób na wykorzystanie potencjału ucznia zdolnego w rozwijaniu kompetencji językowej na poziomie A1/A2 - Gierzyńska, Marta (Neofilolog, 2022)
This article is devoted to the issue of special educational needs in the context of working with a gifted learner, with particular linguistic abilities. Satisfying the needs of such children and providing them with opportunities for integral development of linguistic competence demands a different educational approach – similar to the situation when working with students with some limitations in their learning processes. The approach taken reflects the concepts and definitions of abilities presented in this article. The analysis of those elements suggests ways of identifying gifted learners and, as the next step, also offers certain educational solutions which can easily be applied in teaching. One such way can be preparing children and teenagers for international language certificates in German – Fit in Deutsch 1 and 2 as a form of extra-curricular activities. These certificates are at the A1/A2 level of language skills according to the Common European Framework of Reference for Languages (CEFR). As they are aimed at young people aged 10–16, it is possible to include primary school students in preparation for them, which in turn allows the learners to develop language skills and linguistic interests at the second stage of education. This article serves as a general overview and should not be taken as an empirical research.